2017
DOI: 10.1038/s41598-017-13204-7
|View full text |Cite
|
Sign up to set email alerts
|

Spred2-deficiecy Protects Mice from Polymicrobial Septic Peritonitis by Enhancing Inflammation and Bacterial Clearance

Abstract: Sepsis is an infection-induced systemic inflammatory syndrome and a major cause of death for critically ill patients. Here, we examined whether the absence of Sprouty-related EVH1-domain-containing protein 2 (Spred2), a negative regulator of the Ras/Raf/ERK/MAPK pathway, influences host defense against polymicrobial sepsis (PMS) induced by cecal ligation and puncture (CLP). Compared to wild-type mice, Spred2−/− mice exhibited higher survival rates with increased level of leukocyte infiltration and local chemok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
0
11
1
Order By: Relevance
“…METTL3 depletion attenuated the translation of SPRED2 mediated by YTHDF1. Previous studies have shown that Spred2 -knockout mice have more infiltrating macrophages with an M1 phenotype in mesenteric white adipose tissue 41 and produce significantly higher levels of inflammatory cytokines 42 , which seems to partly differ from our results. The results also indicate that the dynamic plasticity of macrophages is regulated by the local microenvironment, which makes it possible to target macrophages for disease therapy.…”
Section: Discussioncontrasting
confidence: 99%
“…METTL3 depletion attenuated the translation of SPRED2 mediated by YTHDF1. Previous studies have shown that Spred2 -knockout mice have more infiltrating macrophages with an M1 phenotype in mesenteric white adipose tissue 41 and produce significantly higher levels of inflammatory cytokines 42 , which seems to partly differ from our results. The results also indicate that the dynamic plasticity of macrophages is regulated by the local microenvironment, which makes it possible to target macrophages for disease therapy.…”
Section: Discussioncontrasting
confidence: 99%
“…The TLR4 ligand LPS stimulated bone marrow-derived macrophages to produce TNFα and MCP-1 (17). We recently showed that macrophage cytokine response to LPS was partially blocked by U0126 (24), suggesting that Spred2 may be involved in the regulation of the MAPK pathway downstream of TLR4. It is also possible that Spred2 may suppress TLR signaling by other unidentified mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…As the ERK/MAPK pathway is involved in several cellular processes in adipocytes or macrophages, dysregulation of ERK/MAPK signaling could affect diet-induced obesity and obesity-induced adipose tissue inflammation and metabolic abnormalities. We previously reported that Spred2-deficiency in mice exacerbated acetaminophen-induced hepatotoxicity (23), LPS-induced acute lung inflammation (17), D-galactosamine/LPS-induced acute liver injury (18), and polymicrobial septic peritonitis (24). In the present study, we demonstrate, for the first time, that Spred2 plays an important role in regulating the development of diet-induced obesity, obesity-induced adipose tissue inflammation, and metabolic abnormalities, including fatty liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that the production of proinflammatory mediators was up-regulated in Spred2 −/− resident or M-CSF-induced BM-derived macrophages 22 , 23 . Here, we examined the production of TNFα and MCP-1 by inflammatory macrophages obtained by intraperitoneal injection of thioglycolate (TG) in response to BLM or LPS.…”
Section: Resultsmentioning
confidence: 99%